Hubungan Deteksi Dini Kesehatan Mental dengan Academic Burnout Syndrom pada Remaja - Anak Agung Made Ayuni Putri Artati; Ni Luh Putu Thrisna Dewi; Ni Putu Wiwik Oktaviani (Jurnal Akademika Baiturrahim Jambi, 2026)
Early detection of mental health problems among adolescents has become an important issue, especially amid the increasing prevalence of depression and anxiety that may lead to Academic Burnout Syndrome (ABS). This study aimed to determine the relationship between early detection of mental health and Academic Burnout Syndrome among eleventh-grade students at SMA Negeri 8 Denpasar, as well as to identify the direction and strength of the correlation. A quantitative descriptive design with a cross-sectional approach was used. The study was conducted from November 10 to 19, 2024, involving 220 students selected through purposive sampling. Data were collected using mental health and academic burnout syndrome questionnaires and analyzed using the Spearman Rank correlation test. The results showed that 177 respondents (80.5%) were indicated to have mental health problems, with complaints such as anxiety, fatigue, and difficulty concentrating. Most students were categorized as having a low level of Academic Burnout Syndrome (59.5%). Statistical analysis revealed a significant relationship between early detection of mental health and Academic Burnout Syndrome (p-value = 0.001) with a correlation coefficient of -0.383, indicating a weak negative correlation. This means that the better adolescents are at recognizing their mental health conditions early, the lower their risk of experiencing academic burnout. Therefore, schools are encouraged to conduct routine mental health screenings and provide mental health education with support from teachers and parents as a preventive effort against Academic Burnout Syndrome